A single case study on Benign Prostatic Hyperplasia with Dashamoola siddha Taila Uttarbasti - Ninama, Divyabahen S.; Shah, Harshit; Sharma, Rajesh Kumar; Panchal, Sonal; Parmar, Damini (Asian Journal of Pharmaceutical Research and Development, 2023)
BPH is major giriatric problem of obstructive uropathic disorders described in ayurveda as one type of Mutraghata.BPH is a non-malignant enlargement of the prostate gland caused by excess growth of prostatic nodules. Histo-pathologically the prevalence of BPH is age dependent, initiate usually after 40 years of age.The age-specific prevalence of benign prostatic hyperplasia has been estimated from autopsy studies to be 8% in the fourth decade of life, 50% in the sixth decade of life, and 80% in the ninth decade of life. BPH is a progressive disease and In Ayurveda, Mutraghata either upper or it is commonly associated with lower urinary tract symptoms such as retension, incomplete voiding, dribbling, hesitancy, incontinence of urine etc. In morden medicine the management of BPH is either by conservative treatment using chemotherapy, hormonal therapy and surgical approach. In this case study, a patient diagnosed with Benign Prostatic Hyperplasia was treated with a Dashamoola siddha TailaUttarbasti 20 ml once daily for three days and then 3 days gap given between two cycles for 21 days. Assessment of patient was done by IPSS (International Prostate Symptom Score) and weight of the prostate and post void residual urine volume. After completion of Uttarbasti treatment significant relief was observed in symptoms.